2018
DOI: 10.1021/jacs.8b09198
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent Ligand Binding to Cell Membrane Antigens: Defining the Interplay of Affinity, Valency, and Expression Density

Abstract: Nature uses multivalency to govern many biological processes. The development of macromolecular and cellular therapies has largely been dependent on engineering similar polyvalent interactions to enable effective targeting. Such therapeutics typically utilize high-affinity binding domains that have the propensity to recognize both antigen-overexpressing tumors and normal-expressing tissues, leading to “on-target, off-tumor” toxicities. One strategy to improve these agents’ selectivity is to reduce the binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(104 citation statements)
references
References 58 publications
6
98
0
Order By: Relevance
“…19,20,34 We have previously demonstrated that the apparent affinity of a targeted CSAN can be modulated by mixing different ratios of a targeting monomer with a non-targeting monomer, thereby tuning the valency of the scaffold. 36 Accordingly, we chose to explore the effect of various prenylation valencies on each nanoring, with overall valencies ranging from 8-2. Cells were treated with the hybrid prenylated CSANs and incubated for 1 h at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…19,20,34 We have previously demonstrated that the apparent affinity of a targeted CSAN can be modulated by mixing different ratios of a targeting monomer with a non-targeting monomer, thereby tuning the valency of the scaffold. 36 Accordingly, we chose to explore the effect of various prenylation valencies on each nanoring, with overall valencies ranging from 8-2. Cells were treated with the hybrid prenylated CSANs and incubated for 1 h at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Cell Capture and Release: MCF-7, SK-BR-3, MDA-MB-231 cells were harvested and stained with membrane probe DiO, Dil, and nuclear-specific dye Hoechst 33 342 (all purchased from Beyotime), respectively, in PBS at 4°C for 30 min. After three-time wash by PBS, cells were resuspended in PBS, and cell density was measured by a hemocytometer, except that a small cell number (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) was determined as previously reported. A certain number of labeled cells or cell mixtures were spiked with 10 5 Jurkat cells, and incubated with 200 nm biotin-labeled TDN-3 EpCAM, DNA nanosynapse, or cocktail of isotropous TDN-3 (TDN-3 EpCAM:TDN-3 EGFR:TDN-3 HER2 = 1:1:1) respectively in BB buffer at 4°C for 30 min with a final volume of 200 µL.…”
Section: Methodsmentioning
confidence: 99%
“…Multivalent display offers a powerful way to tune and enhance the binding affinity between target receptors and weakly capture ligands. [13][14][15] Several groups have demonstrated the engineering of multivalent aptamer for a lower dissociation constant, giving rise to highly efficient CTCs capture. [16][17][18][19][20][21] As a recent example, one study has taken advantage of DNA framework to control the spatial organization of trivalent aptamers against EpCAM (epithelial cell adhesion molecule).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the range of ligands an adhesin can bind could increase tropism and allow bacteria to migrate from one tissue to another. Avidity and affinity optimization of protein scaffolds for recognition of on- and off-target biomolecules can increase the specificity of cellular targeting ( 31 ). This heteromultivalent binding could be important for increasing specificity for a target tissue ( 26 , 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%